The Determinants of Transportation Mode Choice in the Middle Eastern Cities: the Kerman Case, Iran - Hamid Soltanzadeh; Houshmand E. Masoumi (TeMA: Journal of Land Use, Mobility and Environment, 2014)
Having a precise understanding of the determinants of transportation mode choices and decisions can be under the influence of regional and cultural aspects. This paper outlines such determinants in the Iranian city of Kerman as a representative of the similar Middle Eastern cities located in hot-arid climates and Moslem cultures. The descriptive analysis of the results derived from a short survey that was a part of a larger study conducted in the second half of 2013 indicated that adding to accessibility to public transportation and the convenience of using it can persuade people to shift from car driving to public transit use. The main barriers to bicycling are socio-cultural aspects, while for walking the obstacles are physical and objective. Increasing the quality of pedestrian infrastructure and spaces is a stronger deterrent than personal attitudes against walking. Such findings show slight dissimilarities from the results of some of the western studies that find the built environment more effective. These findings can be a general guide for the Middle Eastern planners to promote walking, biking, and public transport use.